Reproductive aspects of Harttia carvalhoi Miranda Ribeiro, 1939, a small loricariid from streams of serra da Mantiqueira eastern, SP, Brazil - Biagiotto, Renan Hohendorff [UNESP]; Rondineli, Giulianna; Carmassi, Alberto Luciano [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (Revista Biota Neotropica, 2012)
The aim of this work was to present the reproductive aspects of Harttia carvalhoi Miranda Ribeiro, 1939, a small loricariid whose distribution is restricted to the area of drainage basin of the Paraiba do Sul river. A total of 110 specimens of H. carvalhoi were captured. The reproductive period happens from September to February. A total spawning type was identified and fecundity rate ranged from 16 to 106 oocytes. This type of study is important, since fecundity is a specific feature and is adapted to the conditions of the life cycle, varying with growth, population density, food availability and mortality rate. We also emphasize the importance of this study, since there are no previous studies about the reproduction of this species.

O objetivo deste trabalho foi apresentar os aspectos reprodutivos de Harttia carvalhoi, Miranda Ribeiro, 1939, um pequeno loricariídeo cuja distribuição é restrita a área de drenagem do rio Paraíba do Sul. Um total de 110 exemplares de H. carvalhoi foi obtido. O período reprodutivo acontece desde Setembro até Fevereiro. O tipo de desova foi identificado como total e a taxa de fecundidade variou de 16 a 106 ovócitos. Este tipo de estudo é importante, visto que fecundidade é uma característica específica e é uma adaptação às condições do ciclo de vida, variando com o crescimento, densidade populacional, alimentos disponíveis e taxa de mortalidade. Nós também enfatizamos a importância deste estudo, pois não há estudos prévios sobre a reprodução desta espécie.
Aspectos reprodutivos de Harttia carvalhoi Miranda Ribeiro, 1939, um pequeno loricariídeo de riachos do leste da serra da Mantiqueira, SP, Brasil
Keywords: Loricariinae; sex ratio; reproductive period; fecundity; Brazil